2003
DOI: 10.2527/2003.814997x
|View full text |Cite
|
Sign up to set email alerts
|

Prerigor injection using glycolytic inhibitors in low-quality beef muscles1

Abstract: ABSTRACT:The objective of this experiment was to determine the effect of prerigor injection of several glycolytic inhibitors on pH, color, tenderness, and related traits of low-value beef cuts. The semimembranosus, triceps brachii, and supraspinatus muscles from each of 10 steer carcasses were removed 1 h postmortem. Control samples remained in the carcass at 2°C for 24 h. Prerigor muscles were injected and tumbled with 10% (by weight) of one of four solutions: sodium citrate (NaC; 200 mM), sodium fluoride (Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The extreme effects of slaughter on the body (i.e., accelerated anaerobic metabolism, decrease in muscle pH, loss of blood and oxygen supply to the muscle, and loss of homeostasis) were assumed to be somewhat similar to exhaustive anaerobic exercise, but neither CIT nor ACE administration affected postmortem muscle pH conditions in our study. Injection of CIT directly into prerigor beef inhibited postmortem glycolysis and improved tenderness (Jerez et al, 2003). However, injecting CIT into prerigor porcine muscle elevated pH, but neither CIT nor ACE administration had an effect on glycolytic metabolites (Stephens et al, 2006).…”
Section: Postmortem Glycolysis and Early Postmortem Phmentioning
confidence: 99%
“…The extreme effects of slaughter on the body (i.e., accelerated anaerobic metabolism, decrease in muscle pH, loss of blood and oxygen supply to the muscle, and loss of homeostasis) were assumed to be somewhat similar to exhaustive anaerobic exercise, but neither CIT nor ACE administration affected postmortem muscle pH conditions in our study. Injection of CIT directly into prerigor beef inhibited postmortem glycolysis and improved tenderness (Jerez et al, 2003). However, injecting CIT into prerigor porcine muscle elevated pH, but neither CIT nor ACE administration had an effect on glycolytic metabolites (Stephens et al, 2006).…”
Section: Postmortem Glycolysis and Early Postmortem Phmentioning
confidence: 99%
“…It may be related to the potential of SC used as a glycolytic inhibitor for pre-rigor of beef and also be related to the alkalinity of SC itself. [26] The results also shown that a* values of all treatments significantly decreased with storage time. It may be attributed to the oxidation of myoglobin and formation of metmyoglobin.…”
Section: Itemsmentioning
confidence: 71%
“…Most tumor cells have a lower pH value than normal cells. Treatment of prerigor muscle with sodium citrate or sodium fluoride maintained the pH of the muscle at 6.18 and 5.93, respectively (113). Lactic acid formation was prevented, and glycogen breakdown was delayed or inhibited.…”
Section: Therapeutic Strategies For Hypoxia-induced Angiogenic Diseasesmentioning
confidence: 98%